Impact of ischaemic heart disease severity and age on risk of cardiovascular outcome in diabetes patients in Sweden: a nationwide observational study. Issue 4 (3rd April 2019) - Jernberg, Tomas; Lindholm, Daniel; Hasvold, Lars Pål; Svennblad, Bodil; Bodegård, Johan; Sundell Andersson, Karolina; Thuresson, Marcus; Erlinge, David; Janzon, Magnus
Abstract : Objectives: To compare short-term cardiovascular (CV) outcome in type 2 diabetes (T2D) patients without ischaemic heart disease (IHD), with IHD but no prior myocardial infarction (MI), and those with prior MI; and assess the impact on risk of age when initiating first-time glucose-lowering drug (GLD). Design: Cohort study linking morbidity, mortality and medication data from Swedish national registries. Participants: First-time users of GLD during 2007–2016. Outcomes: Predicted cumulative incidence for the CV outcome (MI, stroke and CV mortality) was estimated. A Cox model was developed where age at GLD start and CV risk was modelled. Results: 260 070 first-time GLD users were included, 221 226 (85%) had no IHD, 16 294 (6%) had stable IHD—prior MI and 22 550 (9%) had IHD+MI. T2D patients without IHD had a lower risk of CV outcome compared with the IHD populations (±prior MI), (3-year incidence 4.78% vs 5.85% and 8.04%). The difference in CV outcome was primarily driven by a relative greater MI risk among the IHD patients. For T2D patients without IHD, an almost linear association between age at start of GLD and relative risk was observed, whereas in IHD patients, the younger (<60 years) patients had a relative greater risk compared with older patients. Conclusions: T2D patients without IHD had a lower risk of the CV outcome compared with the T2D populations with IHD, primarily driven by a greater risk of MI. For T2D patients without IHD, an almost linear association between age at start of GLD and relative risk was observed, whereas in IHD patients, the younger patients had a relative greater risk compared with older patients. Our findings suggest that intense risk prevention should be the key strategy in the management of T2D patients, especially for younger patients.